Species identification of voles and lemmings from Late Pleistocene deposits in Pin Hole Cave (Creswell Crags, UK) using collagen fingerprinting. (30th July 2018) - Buckley, Michael; Gu, Muxin; Herman, Jeremy; Junno, Juho-Antti; Denys, Christiane; Chamberlain, Andrew T.
Abstract: Microfaunal remains are commonly used as palaeoenvironmental proxies and have been proposed as a means to identify relative ages of Late Quaternary deposits through biostratigraphy (i.e., utilising 'Mammal Assemblage Zones'). However, assemblages of faunal remains can include a diverse range of taxa which are often difficult to distinguish using morphological aspects of the surviving bones, particularly when diagnostic features are eroded or missing due to fragmentation. Here we investigate the application of a recently developed method of species identification by collagen fingerprinting to arvicoline rodents (voles and lemmings), the dominant mammalian taxonomic group present at the Late Pleistocene site of Pin Hole Cave, Creswell Crags U.K., which is currently the designated British type locality for the Pin Hole Mammal Assemblage Zone (Oxygen Isotope Stage 3) fauna. We also further explore the potential for studying collagen decay rate via deamidations, and their applicability across the species boundary, in terms of its use for relative ageing of remains. Our results demonstrate the ease with which some taxa can be objectively distinguished to genus (e.g. Microtus from Myodes and Lemmus from Dicrostonyx ) and in some cases species (e.g., M. gregalis from M. oeconomus ), but that the potential for relative ageing is complicated by a range of taphonomic factors. The results highlight the potential for this new technique in much larger-scale palaeoenvironmental studies investigating temporal changes in vertebrate biodiversity.